Degree of Development and Functionality of the Water Supply and Sewage Systems in Rural Poland - Jan Pawełek (Barometr Regionalny, 2016)
The development of water supply and sewage systems in rural areas in Poland is presented. Several factors characterizing progress in their construction are analyzed. The scope of analysis covers such factors as the percentage of population using the systems, increase in the length of the water supply and sewage networks, the number of connections to the systems, mean values of water consumption and sewage production for the water supply and sewage system connections, respectively, and the per capita water consumption. The source material is the data published by the Central Statistical Office and results of studies by other authors. Although the development of water supply and sewage systems has accelerated recently, delays in construction continue to be observed, especially in the case of sewage disposal and treatment infrastructure. Compliance by Poland with the decisions regarding its appropriate development in rural areas is a serious problem.